Faktor-Faktor Yang Mempengaruhi Kepatuhan Pasien Dalam Mengkonsumsi Obat Antihipertensi Di Puskesmas Jatinom - Sri Handayani; Rahmi Nurhaini; Tri Jannah Aprilia (STIKES MUHAMMADIYAH KLATEN, 2019)
Many degenerative diseases occur because of an unhealthy lifestyle. One type of degenerative disease is hypertension. Hypertension is a disease that requires long-term therapy, so it requires patient coverage in the treatment needed to control blood pressure and reduce the risk of complications. This study discusses the factors that influence the consideration of patients in taking antihypertensive drugs.This research is a descriptive analytic research with cross sectional design. The population of the study amounted to 1215 with an average of 101 hypertension visits a month. The number of samples taken was 50 respondents by accidental sampling. Measurement of compliance was carried out using the MMAS (Modified Morisky Adherence Scale) questionnaire.The results of this study can be concluded that the factors of sex, level of last education, employment status, duration of hypertension, insurance participation, level of knowledge, access to health services, family support, the role of health workers, and motivation for treatment, have no relationship with compliance in taking antihypertensive drug